Lipid Droplets Protect Aging Mitochondria and Thus Promote Lifespan in Yeast Cells - Kovacs, Melanie; Geltinger, Florian; Verwanger, Thomas; Weiss, Richard; Richter, Klaus; Rinnerthaler, Mark (Frontiers in Cell and Developmental Biology, 2021)
Besides their role as a storage for neutral lipids and sterols, there is increasing evidence that lipid droplets (LDs) are involved in cellular detoxification. LDs are in close contact to a broad variety of organelles where protein- and lipid exchange is mediated. Mitochondria as a main driver of the aging process produce reactive oxygen species (ROS), which damage several cellular components. LDs as highly dynamic organelles mediate a potent detoxification mechanism by taking up toxic lipids and proteins. A stimulation of LDs induced by the simultaneously overexpression of Lro1p and Dga1p (both encoding acyltransferases) prolongs the chronological as well as the replicative lifespan of yeast cells. The increased number of LDs reduces mitochondrial fragmentation as well as mitochondrial ROS production, both phenotypes that are signs of aging. Strains with an altered LD content or morphology as in the sei1∆ or lro1∆ mutant lead to a reduced replicative lifespan. In a yeast strain defective for the LON protease Pim1p, which showed an enhanced ROS production, increased doubling time and an altered mitochondrial morphology, a LRO1 overexpression resulted in a partially reversion of this “premature aging” phenotype.